The Challenges and Glitches Faced by Teachers of Central India during Lockdown and Solutions - et. al., Dr. Anshu Mathur, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
India's education system is most extensive and diverse in the whole world. Indians are pioneers of change. However, the paradox is teaching fraternity in India is slow to accept change. Working from home for school teachers is tough and many of them are bogged out by intense stress, burn out, depression, and anger. During this lockdown period, teachers are facing several issues and challenges at compounded rate. They are working from home and working for home. The goal of this research is to explore the glitches faced by teachers. A questionnaire survey was followed by selecting 100 teachers working from home from Delhi NCR (n=100) randomly to explore and analyze their issues and problems. The results showed that the teachers generally experienced glitches in stress and anger management, work pressure, academic issues, subject content, classes, online assessment and being at loggerheads with parents. Other personal glitches were also there with some participants. Research provides suggestions aimed at addressing the glitches for hassle free conduction of work from home for school teachers. Research Implications: The investigators observed that teachers adapted to the big transformation of online teaching, but the impact was not felt. They were not trained to make a virtual presence felt. This manifested the stress they were already enduring. Practical Implications: The findings of this paper can be used to address the situation as teacher well being contributes to a happy society. Social Implications: The findings of this paper reveal that women even today bear a lot of responsibility and issues like layoffs and pay cuts have huge impact on their confidence and power of resilience. Female teachers especially wanted to contribute in a better way and wanted training to improvise their virtual teaching.